2016
DOI: 10.1111/jcpe.12547
|View full text |Cite|
|
Sign up to set email alerts
|

Soft tissue volume alterations after connective tissue grafting at teeth: the subepithelial autologous connective tissue graft versus a porcine collagen matrix – a pre‐clinical volumetric analysis

Abstract: Ten months after soft tissue thickening, the CM is statistically non-inferior to the SCTG in terms of soft tissue volume and thickness increase. Further 3D studies are needed to confirm the data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
61
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 29 publications
4
61
0
7
Order By: Relevance
“…VCMX in contrast does not demonstrate any encapsulation, making it more prone to undergo remodeling processes. A higher shrinkage rate of collagen matrices compared to SCTGs over time has previously been reported [37]. In that particular study, 70% (SCTG) and 99% (collagen matrix) of the augmented volumes were lost during a 10-month healing period.…”
Section: Discussionsupporting
confidence: 56%
“…VCMX in contrast does not demonstrate any encapsulation, making it more prone to undergo remodeling processes. A higher shrinkage rate of collagen matrices compared to SCTGs over time has previously been reported [37]. In that particular study, 70% (SCTG) and 99% (collagen matrix) of the augmented volumes were lost during a 10-month healing period.…”
Section: Discussionsupporting
confidence: 56%
“…Collagen matrix (CM) is routinely used as a biocompatible material for soft tissue augmentation. Xenogeneic CM achieved acceptable tissue volume and thickness increases, minimal pain in patients, and no evidence of infections compared to autogenous transplants based on several preclinical and clinical studies (Herford, Akin, Cicciu, Maiorana, & Boyne, ; Schmitt et al, ; Schmitt et al, ; Thoma et al, ; Thoma, Naenni, Benic, Hämmerle, & Jung, ). To improve the high shrinkage of natural noncross‐linked CM (ncl_CM), cross‐linked CM (cl_CM) was proposed, which could maintain a stable tissue volume because enzymatic degradation was controlled, resulting in slower degradation (Herford, Nguyen, Miller, Tandon, & Signorino, ; Huber, Zeltner, Hämmerle, Jung, & Thoma, ; Rothamel et al, ; Thoma et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A porcine acellular dermal collagen matrix (CM) has been introduced as an alternative to SCTGs in order to avoid surgical risks and to decrease patient morbidity . These matrices proved their ability to increase soft tissue thickness in preclinical animal studies . In a comparative dog study, a porcine CM has shown similar results as SCTG after a 10‐month follow‐up .…”
Section: Introductionmentioning
confidence: 99%